Development and Validation of A Reverse Phase HPLC Method for the Determination of Metformin HCl in Pharmaceutical Dosage Forms - Sreenivasa Rao, Battula; Shankar Dubey, Som; Nagendar Rao, K.; Venkata Kiran, B. (Asian Journal of Chemistry, 2012)
Metformin hydrochloride chemically, N,N-dimethyl imido dicarbonimidicdiamide hydrochloride is used as antidiabetic drug from the biguanide class used in the management of type 2 diabetes. A rapid specific reverse-phase HPLC method has been developed for assaying metformin HCl in pharmaceutical dosage forms. The method involves an isocratic elution of drug in a Zorbax-SCX, C18, 250 mm × 4.6 mm, 5 mm column using a mobile phase composition of Buffer (pH 3.0) with ammonium dihydrogen phosphate: acetonitrile [50: 50, v/v] with flow rate of 1.0 mL/min at 218 nm. The developed method is found to be linear in the range of 20-60 μg/ mL. The method has been validated for specificity, linearity, range, precision, accuracy, limit of detection, limit of quantification, ruggedness and robustness. The % recovery of metformin hydrochloride was found to be in the range of 99.22-100.11 %.